PERANCANGAN BUSINESS CONTINUITY PLAN BERBASIS RISIKO PADA RSUD ARIFIN ACHMAD PEKANBARU - Syahril M.Kom -; Dwi Muhammad Iqbal; Risnal Diansyah, MTI (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2021)
This study aims to provide guidance on the preparation of a Business Continuity Plan (BCP) document framework, which is tailored specifically to the needs and conditions of the company regarding business sustainability. The preparation of the framework is the result of the formulation between the needs and conditions of the company and the best practice framework of ISO 22301: 2012, as well as other related research. This will provide the results of a framework that is appropriate and specific to the conditions and needs of the company.The case study in this study was Arifin Achmad Hospital (Regional General Hospital), Pekanbaru. To improve customer service, this company uses information technology as a supporting resource for its daily operations. So that BCP will be a solution to help companies overcome disruptions and threats that can disrupt the performance of the company's information technology.This research was conducted with ISO 27001:2012 risk analysis method and FMEA method with ISO 31000: 2009 risk management stages combined with an analysis of the risk impacts of ISO 22317: 2015 and the ISO 22301: 2012 BCMS Framework. The results of the framework willbe verified and validated through confirmation and validation on the company. This research shows that BCP in each company is unique and different